The Volunteer Satisfaction Survey (VSS): Adaptation and Psychometric Properties among Portuguese Volunteers - Martins, Cátia (2022)
(1) Background: Volunteering satisfaction is one significant construct that nourishes the sustaining of volunteer work, and it is present in reference models such as the three-stage volunteer process model (VPM). The volunteer satisfaction survey (VSS), created by Vecina, Chacón and Sueiro, evaluates three different domains of volunteer satisfaction: specific motivations, organization management and volunteering tasks. The aim of this study was to adapt the instrument and explore the psychometric properties of the 17 items of the VSS in a sample of Portuguese volunteers. (2) Methods: The sample was composed of 335 Portuguese volunteers (aged between 14 and 81 years), mainly women (76.4%). Measures included volunteer satisfaction, work engagement and organizational commitment. (3) Results: The original three-factor model was tested with a confirmatory factor analysis (CFA) and the model fitted the data. Satisfactory levels of internal consistency, discriminant and convergent validity were found. (4) Conclusions: The VSS reveals good psychometric properties and can be considered a useful tool for professionals and future research for volunteers' satisfaction assessment.